Hydrophilic PPy / 3DRGO / WSP5 composite material and preparation method and application thereof

By combining WSP5, 3DRGO and Py in one-step hydrothermal method, a hydrophilic PPy/3DRGO/WSP5 aerogel composite material was prepared, which solved the problem of insufficient conductivity and dispersion of composite electrode materials in the prior art, and achieved high efficiency , simple preparation method and excellent electrochemical properties.

CN114994149BActive Publication Date: 2025-02-07YANGZHOU UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210576716.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-25
Publication Date
2025-02-07
Estimated Expiration
2042-05-25

AI Technical Summary

Technical Problem

The prior art is difficult to prepare composite electrode materials with good conductivity, morphology and dispersion, especially in improving electrochemical properties and simplifying the preparation method.

Method used

By a one-step hydrothermal method, a water-soluble cationic quaternary ammonium column [5]aromatic hydrocarbon (WSP5) was compounded with three-dimensional reduced graphene oxide (3DRGO) and polypyrrole (Py) to prepare hydrophilic PPy/3DRGO/WSP5 aerosol Glue composite material.

Benefits of technology

The preparation of composite materials with good conductivity, dispersion and electrochemical properties is realized, the preparation process is simplified, the reaction time and temperature are reduced, and the material has a three-dimensional multi-porous structure and good water dispersion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114994149B_ABST
    Figure CN114994149B_ABST
Patent Text Reader

Abstract

The invention discloses a hydrophilic PPy / 3DRGO / WSP5 composite material and a preparation method and application thereof. The method adopts a one-step synthesis method, uses water-soluble cationic quaternized pillar [5] aromatic hydrocarbon and graphene oxide as raw materials, adds pyrrole, mixes evenly and then undergoes hydrothermal reaction to obtain a hydrophilic PPy / 3DRGO / WSP5 aerogel composite material. The hydrophilic PPy / 3DRGO / WSP5 aerogel composite material of the invention has the electrical conductivity of three-dimensional graphene and polypyrrole, the excellent hydrophilic property of WSP5, and a porous structure, and is suitable for use as a conductive material in electrochemical sensors, batteries, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite electrode materials and relates to a hydrophilic PPy / 3DRGO / WSP5 composite material and a preparation method and application thereof. Background Art

[0002] Pillararene (PA) is a three-dimensional columnar molecule composed of n hydroquinones. It has high symmetry and rigidity, which enables it to selectively bind to guests. Pillararenes are stable in conformation and the groups on them are replaceable, so they can perform host-guest recognition on a variety of guest molecules. Electrochemical sensors based on host-guest interactions have been widely used in the analysis and detection of various metal ions, small molecules, etc. However, pillararene[5] itself has no conductivity.

[0003] Compared with graphene, three-dimensional graphene has a higher specific surface area, better mechanical properties and porosity, and has been widely used in energy storage, catalysts, environmental protection, stretchable conductors, etc.

[0004] Polypyrrole is an electronically conductive polymer material, which is mainly prepared by chemical oxidation and electrochemical synthesis. The chemical oxidation method is to add a specific oxidant to the reaction medium to oxidize the pyrrole monomer to obtain polypyrrole. In the chemical oxidation method, the reaction medium, oxidant and monomer concentration all have an impact on the reaction. Commonly used reaction media are water, acetonitrile and ether, and commonly used oxidants are ferric chloride, dichromate and hydrogen peroxide. The polypyrrole prepared by the chemical oxidation method has low cost, simple process and convenient operation, but the prepared polypyrrole is insoluble and infusible, and is not easy to process. The electrochemical synthesis method uses the overpotential as the initiation and reaction driving force to polymerize the pyrrole monomer on the electrode to obtain a polypyrrole film. In the electrochemical synthesis method, factors such as polymerization potential, current, and electrolyte solution have an impact on polymerization. The polypyrrole prepared by the electrochemical synthesis method has the characteristics of low cost, high purity, single product, simple process, and environmental friendliness, and the performance of the polypyrrole film is controlled by electrochemical parameters, but the yield is low and not suitable for production.

[0005] The literature (Palanisamy S, Thangavelu K, Chen SM, et al. Synthesis and characterization of polypyrroledecorated graphene / β-cyclodextrin composite for low level electrochemical detection of mercury(II) in water[J]. Sensors and Actuators B: Chemical, 2017, 243: 888-94.) synthesized a GR-CD / PPy material, but it was not a three-dimensional structure and had large defects, and the enrichment time before DPV scanning was too long. Summary of the invention

[0006] The object of the present invention is to provide a hydrophilic PPy / 3DRGO / WSP5 composite material with simple preparation method, orderly morphology and good conductivity, as well as a preparation method and application thereof.

[0007] The technical solution for achieving the purpose of the present invention is as follows:

[0008] The preparation method of the hydrophilic PPy / 3DRGO / WSP5 composite material comprises the following steps:

[0009] Water-soluble cationic quaternized pillar[5]arene (WSP5) was dispersed in a graphene oxide (GO) aqueous solution, and then pyrrole (Py) was added and stirred until the mixture was uniformly mixed. The mixture was hydrothermally reacted at 90°C for 3 h. After the reaction, the hydrogel was obtained by centrifugation and washing, and finally freeze-dried to obtain a hydrophilic PPy / 3DRGO / WSP5 aerogel composite material.

[0010] Preferably, the mass ratio of water-soluble cationic quaternized pillar [5] aromatic hydrocarbon to graphene oxide is 37:80, and the composite material prepared at this ratio has the best dispersibility.

[0011] Preferably, the concentration of graphene oxide is 5 mg mL -1 Under this condition, the composite material is easy to form.

[0012] Preferably, the mass ratio of pyrrole to graphene oxide is 1333:4000. The present invention uses only a small amount of Py to complete the reduction, and the reaction time is short and the temperature is low.

[0013] Preferably, the freeze-drying time is 48 h.

[0014] Compared with the prior art, the present invention has the following advantages:

[0015] (1) In the present invention, three-dimensional reduced graphene oxide (3DRGO) has good electrical conductivity. After water-soluble cationic quaternized pillar [5] aromatic hydrocarbons, graphene oxide and polypyrrole are compounded to form a hydrophilic PPy / 3DRGO / WSP5 aerogel composite material, not only the dispersibility of the material can be effectively improved, but also the electrochemical performance of the material can be further improved. Compared with single H-3DRGO and PPy / 3DRGO, the hydrophilic PPy / 3DRGO / WSP5 aerogel composite material prepared by the present invention has moderate defects and better dispersibility. It has the advantages of solubility and host-guest recognition of WSP5, and at the same time has the excellent electrical properties of H-3DRGO and PPy, and is an electrochemical material with good application prospects.

[0016] (2) The present invention adopts a one-step hydrothermal method, which has a simple preparation method, a short reaction time, and a good product morphology. The reaction time is just long enough to fully reduce GO. The composite material prepared by the present invention has the advantages of a three-dimensional porous structure, small defects, and a short detection time. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Scanning electron microscopy images of PPy / 3DRGO / WSP5-10 min (a1~a3) and PPy / 3DRGO / WSP5 (b1~b3).

[0018] Figure 2 TEM image of PPy / 3DRGO / WSP5.

[0019] Figure 3 Infrared images of PPy / 3DRGO / WSP5, WSP5, H-3DRGO, PPy / 3DRGO and PPy.

[0020] Figure 4 UV images of PPy / 3DRGO / WSP5, WSP5, H-3DRGO and PPy / 3DRGO.

[0021] Figure 5 Raman images of PPy / 3DRGO / WSP5, H-3DRGO and PPy / 3DRGO.

[0022] Figure 6 The water dispersibility diagrams of PPy / 3DRGO / WSP5, H-3DRGO and PPy / 3DRGO.

[0023] Figure 7 Thermogravimetric diagrams of PPy / 3DRGO / WSP5, PPy, WSP5 and PPy / 3DRGO.

[0024] Figure 8For PPy / 3DRGO / WSP5 / GCE, H-3DRGO / GCE, PPy / 3DRGO / GCE and GCE in 5.0 mM [Fe(CN)6] 3- / 4- Cyclic voltammogram in electrolytic solution.

[0025] Fig. 9 For PPy / 3DRGO / WSP5 / GCE, H-3DRGO / GCE, PPy / 3DRGO / GCE and GCE in 5.0 mM [Fe(CN)6] 3- / 4- Electrochemical impedance spectroscopy in electrolytic solution.

[0026] Fig.10 DPV diagram of different concentrations of CBZ in PPy / 3DRGO / WSP5 / GCE sensor (a1), and the linear relationship between CBZ concentration and current (a2). DETAILED DESCRIPTION

[0027] The present invention is further described in detail below in conjunction with the embodiments and drawings.

[0028] The preparation of the water-soluble cationic quaternized pillar [5]arene (WSP5) of the present invention is based on the literature [Ma Y, JiX, Xiang F, et al. Acationic water-soluble pillar [5]arene: synthesis and host-guest complexation with sodium 1-octanesulfonate [J]. Chem Commun (Camb), 2011, 47 (45): 12340-2.], and the specific steps are as follows:

[0029] A 500 mL round-bottom flask was filled with nitrogen and nitrogen protection was applied throughout the process. 3.37 g of 1,1-dibromophenylene diethyl ether was weighed and placed in the 500 mL round-bottom flask. 150 mL of dichloromethane was added and stirred thoroughly to dissolve. 1.047 g of polyformaldehyde was weighed and added to the round-bottom flask. After stirring for 10 min, 1.6 mL of boron trifluoride ether was weighed and added to the round-bottom flask. Stirred for 1 h at 30 °C. After the liquid in the round-bottom flask turned dark green, 200 mL of anhydrous methanol was added to terminate the reaction. The heating was stopped and stirring was continued for 30 min. Stirring was then stopped and the mixture was allowed to stand for 30 min. The crude product was filtered off by suction. Column chromatography was performed using a 1:1 volume ratio of petroleum ether and dichloromethane as the eluent for column chromatography separation. The solvent was removed by rotary evaporation at 30 °C to obtain a white powdery substance. The product was placed in a vacuum dryer at 60 °C for 24 h. After drying, pure brominated column [5] aromatics were obtained.

[0030] Weigh 1.00 g of brominated column [5] aromatic hydrocarbon in a 200 mL round-bottom flask, dissolve it in 50 mL of anhydrous ethanol as solvent, add 6.43 mL of trimethylamine (33 wt.%) solution, stir and reflux at 80 ° C for 12-15 h. After stopping the reaction, remove the solvent by rotary evaporation at 40 ° C. Add 20 mL of deionized water to the obtained solid, filter it to obtain a clear solution, and remove water by rotary evaporation to obtain a colorless solid as pure WSP5.

[0031] Example 1

[0032] Aspirate 8mL 5mg·mL -1 GO aqueous solution was placed in a brown glass bottle, 0.0185g WSP5 was added to the GO aqueous solution, ultrasonically mixed for 30 minutes, and then a stirrer was added to form solution A. Magnetic stirring was performed for 14 hours. After stirring, 13.33mg Py was weighed and evenly dispersed in 8mL solution A, ultrasonically mixed for 30 minutes, and solution B was obtained. Solution B was transferred into a polytetrafluoroethylene-lined hydrothermal reactor and placed in a 90℃ forced air drying oven for reaction for 3 hours. The product was taken out and heated at 10000rmp·min -1 The mixture was centrifuged and washed for 10 min for three times to obtain PPy / 3DRGO / WSP5 black hydrogel, which was then freeze-dried for 48 h to obtain PPy / 3DRGO / WSP5 aerogel composite material, referred to as PPy / 3DRGO / WSP5.

[0033] Comparative Example 1

[0034] Take 8mL of evenly dispersed 5mg·mL -1 GO aqueous solution was placed in a glass bottle and ultrasonicated for about 30 minutes to form solution C. 13.33 mg of Py was added to solution C and the mixture was covered and ultrasonicated for 30 minutes to obtain solution D. Solution D was transferred to a reactor or a glass bottle and placed in a forced air drying oven at 90°C for 3 hours. The product was taken out and rinsed three times with deionized water to obtain a black hydrogel. It was then freeze-dried for 48 hours to obtain PPy / 3DRGO aerogel, referred to as PPy / 3DRGO.

[0035] Comparative Example 2

[0036] Take 8mL of evenly dispersed 5mg·mL -1 The GO aqueous solution was placed in a glass bottle and ultrasonicated for about 30 minutes to form solution C. Solution C was transferred to a reactor or glass bottle and placed in a forced air drying oven at 90°C for 3 hours. The product was taken out and washed three times with deionized water by centrifugation for 10 minutes to obtain a dark brown hydrogel. It was then freeze-dried for 48 hours to obtain H-3DRGO aerogel, referred to as H-3DRGO.

[0037] Comparative Example 3

[0038] Aspirate 8mL 5mg·mL -1 GO aqueous solution was placed in a brown glass bottle, 0.0185g WSP5 was added to the GO aqueous solution, ultrasonically mixed for 30 minutes, and then a stirrer was added to form solution A. Magnetic stirring was performed for 14 hours. After stirring, 13.33mg Py was weighed and evenly dispersed in 8mL solution A, and ultrasonically mixed for about 30 minutes to obtain solution B. Solution B was transferred into a polytetrafluoroethylene-lined hydrothermal reactor and placed in a 90℃ forced air drying oven for reaction for 10 minutes. The product was taken out and heated at 10000rmp·min -1 The PPy / 3DRGO / WSP5 black hydrogel was obtained by centrifugal washing for 10 min three times, and then freeze-dried for 48 h to obtain the PPy / 3DRGO / WSP5 aerogel composite material, referred to as PPy / 3DRGO / WSP5-10 min.

[0039] Comparative Example 4

[0040] Aspirate 8mL 5mg·mL -1 GO aqueous solution was placed in a brown glass bottle, 0.0185 g WSP5 prepared in step (1) was added to the GO aqueous solution, ultrasonically mixed for 30 min, and then a stirrer was added to form solution A. Magnetic stirring was performed for 14 h. After stirring, 13.33 mg Py was weighed and evenly dispersed in 8 mL A, and ultrasonically mixed for about 30 min to obtain solution B. B was transferred to a polytetrafluoroethylene-lined hydrothermal reactor and placed in an 80°C forced air drying oven for reaction for 3 h. The product was taken out and heated at 10000 rmp·min -1 The PPy / 3DRGO / WSP5 black hydrogel was obtained by centrifugal washing for 10 min three times, and then freeze-dried for 48 h to obtain the PPy / 3DRGO / WSP5 aerogel composite material, referred to as PPy / 3DRGO / WSP5-80℃.

[0041] Comparative Example 5

[0042] Aspirate 8mL 5mg·mL -1 GO aqueous solution was placed in a brown glass bottle, 0.0185 g WSP5 prepared in step (1) was added to the GO aqueous solution, ultrasonically mixed for 30 min, and then a stirrer was added to form solution A. Magnetic stirring was performed for 14 h. After stirring, 13.33 mg Py was weighed and evenly dispersed in 8 mL A, and ultrasonically mixed for about 30 min to obtain solution B. B was transferred to a polytetrafluoroethylene-lined hydrothermal reactor and placed in a 75°C forced air drying oven for reaction for 3 h. The product was taken out and heated at 10000 rmp·min -1The PPy / 3DRGO / WSP5 black hydrogel was obtained by centrifugal washing for 10 min three times, and then freeze-dried for 48 h to obtain the PPy / 3DRGO / WSP5 aerogel composite material, referred to as PPy / 3DRGO / WSP5-75℃.

[0043] Application Examples

[0044] (1) The glassy carbon electrode (GCE) was soaked in water and then ground on suede with 0.05 μm Al2O3 powder for 3-5 min. The ground GCE was then placed in a beaker containing anhydrous ethanol and ultrasonicated for 30 s. After the ultrasonication, it was rinsed with deionized water. Then, it was placed in a beaker containing deionized water and ultrasonicated for 30 s. After that, it was rinsed with deionized water again. Finally, the surface of the GCE was blown clean with nitrogen.

[0045] 1 mg·mL -1 After the solution of the hydrophilic PPy / 3DRGO / WSP5 aerogel composite material is evenly dispersed, 4 μL of the solution is dropped on the center of a clean electrode. After it is naturally dried, PPy / 3DRGO / WSP5 / GCE is obtained.

[0046] 5 mg of hydrophilic PPy / 3DRGO / WSP5 aerogel composite was placed in 5 mL of deionized water and ultrasonicated for 5 min to obtain 1 mg mL -1 The hydrophilic PPy / 3DRGO / WSP5 aerogel composite material solution was prepared. The PPy / 3DRGO and H-3DRGO material solutions were also prepared in the same way.

[0047] 1 mg·mL -1 After the PPy / 3DRGO aerogel composite material solution is evenly dispersed, 4 μL of the solution is dropped on the center of a clean electrode. After it is naturally dried, PPy / 3DRGO / GCE is obtained.

[0048] 1 mg·mL -1 After the H-3DRGO aerogel composite material solution is evenly dispersed, 4 μL of the solution is dropped on the center of a clean electrode. After it is naturally dried, H-3DRGO / GCE is obtained.

[0049] After the electrode was prepared, 5.0 mM [Fe(CN)6] 3- / 4- The performance was measured in an electrolytic solution.

[0050] (2) A PPy / 3DRGO / WSP5 / GCE electrochemical sensor was constructed to perform DPV scanning on carbendazim (CBZ). The experimental conditions were: 4 mg electrode modification amount, pH = 6.0 PBS electrolyte, scanning range 0.6-1.2 V, pulse amplitude 0.05 V, pulse width 0.06 s, sampling width 0.02 s, pulse period 0.5 s, standing time 2 s, sensitivity 10 -5 A / V.

[0051] like Figure 1 As shown in the figure, the hydrophilic PPy / 3DRGO / WSP5 aerogel composite material presents a three-dimensional network-like cross-linked, loose and porous structure; the PPy / 3DRGO / WSP5-10 min composite material has a thicker wall, fewer pores and smaller pore size.

[0052] like Figure 2 As shown, the PPy / 3DRGO / WSP5 aerogel composite material becomes thicker at the edge, and irregular spherical substances appear in some parts.

[0053] like Figure 3 As shown in the figure, compared with PPy / 3DRGO / WSP5, PPy / 3DRGO and H-3DRGO, PPy / 3DRGO contains the characteristic peaks of WSP5 and PPy, and the characteristic peaks of oxygen-containing functional groups of GO are greatly weakened, which proves that the preparation of PPy / 3DRGO / WSP5 is successful.

[0054] like Figure 4 As shown, compared with PPy / 3DRGO / WSP5, PPy / 3DRGO and H-3DRGO, the absorption peak of WSP5 is included, which proves that the preparation of the composite material is successful.

[0055] like Figure 5 As shown, PPy / 3DRGO / WSP5 has moderate defects compared with PPy / 3DRGO and H-3DRGO.

[0056] Depend on Figure 6 As shown, PPy / 3DRGO / WSP5 has better dispersibility than PPy / 3DRGO and H-3DRGO.

[0057] like Figure 7 As shown, the loading amount of WSP5 in PPy / 3DRGO / WSP5 was 19%.

[0058] like Figure 8 As shown, the peak current of PPy / 3DRGO / WSP5 / GCE is significantly increased compared with PPy / 3DRGO / GCE, H-3DRGO / GCE and GCE, indicating an increase in the electron transfer rate.

[0059] like Fig. 9 As shown, compared with PPy / 3DRGO / GCE, H-3DRGO / GCE and GCE, it is obvious that the impedance of PPy / 3DRGO / GCE, H-3DRGO / GCE and GCE is significantly greater than that of PPy / 3DRGO / WSP5 / GCE. This shows that the conductivity of PPy / 3DRGO / WSP5 aerogel composite material is better.

[0060] like Fig.10 As shown, DPV scanning was performed on different concentrations of CBZ, and it was found that the PPy / 3DRGO / WSP5 / GCE electrochemical sensor had a good linear relationship in the range of 0.4-200 / 200-1400 μM, and the minimum detection limit was 0.08 μM (S / N=3).

[0061] In summary, the hydrophilic PPy / 3DRGO / WSP5 aerogel composite material synthesized by the present invention has uniform pore distribution, good electrical conductivity and cycle stability. The present invention mainly utilizes the electrochemical properties of three-dimensional reduced graphene oxide and polypyrrole. After reacting with WSP5, not only its electrochemical performance and overall morphology are not greatly affected, but also the water dispersibility of H-3DRGO and PPy / 3DRGO is improved, and the electrochemical performance is also significantly improved. PPy / 3DRGO / WSP5 maintains the porous advantages and electrical conductivity of three-dimensional reduced graphene oxide aerogel while having the good water solubility and host-guest recognition of WSP5. The hydrophilic PPy / 3DRGO / WSP5 aerogel composite material prepared by the present invention is used for electrode materials, and its electrochemical performance is significantly improved compared with H-3DRGO and PPy / 3DRGO, and has good electrical conductivity.

Claims

1. A method for preparing a hydrophilic PPy / 3DRGO / WSP5 composite material, characterized in that: The following steps are involved: Water-soluble cationic quaternized columnar [5] aromatic hydrocarbon was dispersed in the graphene oxide aqueous solution, and then pyrrole was added and stirred until the mixture was uniformly mixed. The mixture was hydrothermally reacted at 90 °C for 3 h. After the reaction, the hydrogel was obtained by centrifugation and washing, and finally freeze-dried to obtain a hydrophilic PPy / 3DRGO / WSP5 aerogel composite material. The mass ratio of water-soluble cationic quaternized columnar [5] aromatic hydrocarbon to graphene oxide was 37:80, and the mass ratio of pyrrole to graphene oxide was 1333:4000.

2. The preparation method according to claim 1, characterized in that The concentration of graphene oxide is 5 mg mL -1 .

3. The preparation method according to claim 1, characterized in that The freeze-drying time was 48 h.

4. The PPy / 3DRGO / WSP5 composite material prepared according to the preparation method according to any one of claims 1 to 3.

5. Use of the PPy / 3DRGO / WSP5 composite material according to claim 4 in electrochemical detection of carbendazim.

Citation Information

Patent Citations

  • Electrochemical sensor for detecting content of carbendazim in fog drops as well as preparation and application methods

    CN103645237A